2019
DOI: 10.1001/jama.2019.11642
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tandem Autologous Stem Cell Transplant vs Single Transplant on Event-Free Survival in Patients With High-Risk Neuroblastoma

Abstract: chemotherapy followed by high-dose therapy with autologous stem cell transplant and subsequent antidisialoganglioside antibody immunotherapy is standard of care for patients with high-risk neuroblastoma, but survival rate among these patients remains low. OBJECTIVE To determine if tandem autologous transplant improves event-free survival (EFS) compared with single transplant. DESIGN, SETTING, AND PARTICIPANTS Patients were enrolled in this randomized clinical trial from November 2007 to February 2012 at 142 Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
344
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(357 citation statements)
references
References 47 publications
10
344
1
2
Order By: Relevance
“…The first block, induction, includes high-dose chemotherapy and resection of the primary tumor. The second block is consolidation, which consists of tandem courses of myeloablative dose chemotherapy with autologous stem-cell rescue and external-beam radiotherapy (Park et al, 2019). Lastly, post-consolidation therapy includes anti-ganglioside 2 (GD2) immunotherapy with cytokines and cis-retinoic acid (Yu et al, 2010).…”
Section: Treatmentmentioning
confidence: 99%
“…The first block, induction, includes high-dose chemotherapy and resection of the primary tumor. The second block is consolidation, which consists of tandem courses of myeloablative dose chemotherapy with autologous stem-cell rescue and external-beam radiotherapy (Park et al, 2019). Lastly, post-consolidation therapy includes anti-ganglioside 2 (GD2) immunotherapy with cytokines and cis-retinoic acid (Yu et al, 2010).…”
Section: Treatmentmentioning
confidence: 99%
“…Median reported age of presentation in the literature is between 46 and 60 years, 4 however, there are case reports of younger individuals, with the youngest being 14‐years old, who developed features similar to PPFE after exposure to cyclophosphamide 5 and a 16‐year old with idiopathic PPFE 6 . While more patients with high‐risk neuroblastoma are surviving, thanks to intensive multimodal chemotherapy, 1 long‐term follow‐up studies have revealed that survivors are at a higher risk of treatment‐related complications including dysfunction of musculoskeletal, neurologic, endocrinal, sensory, cardiovascular, renal, and pulmonary function in addition to increased rates of secondary malignancies 7 . Specific pulmonary complications described include chronic respiratory symptoms, abnormal PFT, and bronchiectasis 7 …”
Section: Discussionmentioning
confidence: 99%
“…The patient was diagnosed at age 3 with stage four, high‐risk neuroblastoma. Her treatment consisted of six cycles of induction chemotherapy including cisplatin, etoposide, vincristine, cyclophosphamide, doxorubicin, and topotecan per Children's Oncology Group (COG) protocol ANBL0532 1 . She achieved a complete response and proceeded with conditioning chemotherapy with carboplatin, etoposide, and melphalan followed by autologous stem cell rescue and radiation to her resected adrenal tumor bed.…”
Section: Case Descriptionmentioning
confidence: 99%
“…In particular, the antidisialoganglioside (anti-GD2) immunotherapy has recently been successfully incorporated into the standard of care treatment for high-risk NB patients [8]. Moreover, a recent randomized clinical trial (NCT00567567) has demonstrated that tandem autologous stem cell transplant with thiotepa/cyclophosphamide followed by carboplatin/etoposide/melphalan resulted in a significantly better EFS than single transplantation with carboplatin/etoposide/melphalan in high-risk NB patients under 30 years of age [9]. Several innovative strategies aimed at targeting the tumor microenvironment, the noradrenaline transporter, and the genetic pathways are being developed with promising effects in NB diagnosis and treatment [7].…”
Section: Neuroblastoma (Nb)mentioning
confidence: 99%